Utilization of Inulin-enriched Honey Powder as a Sugar Substitute to Enhance the Functional and Sensory Quality of Prebiotic Biscuits - Jaya, Firman; Andriani, Ria Dewi; Wahyuni, Rini Dwi; Bahrun, Esthalia Kustin Pasole; Parlan (Jurnal Ilmu-Ilmu Peternakan, 2025)
The growing concern regarding excessive sugar intake and its link to chronic health conditions has driven innovations in functional food development, particularly through the use of natural sugar alternatives. This study aimed to investigate the effects of substituting sugar with inulin-enriched honey powder on physical, sensory, and microstructural characteristics, as well as selected chemical properties (moisture and ash) of prebiotic biscuits. A laboratory experiment with a completely randomized design with five treatments and four replications was conducted. Biscuits were formulated with varying ratios of powdered sugar and inulin honey powder: 100:0, 75:25, 50:50, 25:75, and 0:100. The measurements included diameter, thickness, spread ratio, hardness, color (L*, a*, b*), sensory attributes (color, aroma, taste, hardness, overall acceptance), and microstructure by scanning electron microscopy. The results revealed that increasing the proportion of inulin honey powder significantly (P < 0.01) reduced the diameter and thickness but improved the spread ratio. The 50:50 sugar-to-honey powder ratio presented the best combination of physical characteristics and sensory acceptance. Biscuits from this formulation had a favourable spread ratio, lower hardness, and a homogeneous microstructure. Sensory evaluation indicated that moderate substitution preserved desirable taste and hardness. These findings demonstrate that inulin honey powder can serve as a viable natural sweetener in baked goods while improving textural and structural quality. This approach contributes to the development of healthier food options and supports future applications of natural prebiotic sweeteners in functional bakery products.